Time to WISE up - Abd Razak, Dzulkifli (2009)
How much does it cost to deploy one American soldier in Afghanistan? It is equivalent to running at least 40 schools! So the audience at the inaugural World Innovation Summit for Education (WISE) were informed when the event opened in Doha, Qatar last week. Imagine how many educational opportunities which are badly needed in Afghanistan have been squandered on soldiers. Till today, there is no end in sight to this crisis. One delegate suggests that a "teaching" force rather than an "invading" one is more effective to win the hearts and minds of the people.